Amamentação e economia : influência do parceiro íntimo na formação inicial do capital humano - uma revisão sistemática e análise empírica - Santos, Camilla Oliveira (2024)
In this research, two distinct methods were explored to evaluate the impact of domestic and family violence against women on the first form of postnatal human capital investment: breastfeeding. The first essay consists of a systematic literature review using the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), which rigorously synthesizes the evidence on the effects of intimate partner violence (IPV) on breastfeeding quality. The analysis revealed that IPV negatively impacts breastfeeding across various geographic contexts, although few studies disaggregate the types of violence or use longitudinal data sets. The second essay is empirical in nature and uses novel data from the 2019 Survey on Socioeconomic Conditions and Domestic and Family Violence against Women (PCSVDF). To investigate the impact of partner behavior on exclusive breastfeeding, a two-stage econometric model was employed. In the first stage, the scalar breastfeeding variable was transformed into a count variable with conditional probability, while the second stage consisted of a count regression. The results demonstrated that partner behavior has a statistically significant effect on exclusive breastfeeding when the data is segregated by region. Other factors, such as the mother’s desire to become pregnant, history of fertility issues, ethnicity, and the baby’s birth weight, were also relevant. This study stands out for its innovative use of a systematic review in economics and for applying a systematic review methodology within the economic context, based on the argument that breastfeeding is the first postnatal investment in human capital. In addition to the innovation of using a systematic review in the economic field, the use of data sets such as the PCSVDF contributes to expanding knowledge in this area. The findings highlight the importance of public policies that promote exclusive breastfeeding and specific approaches to addressing domestic violence in different socioeconomic and geographic contexts. This work offers valuable insights for future research and interventions in the fields of maternal and child health and economic development.